2019
DOI: 10.30802/aalas-jaalas-19-000004
|View full text |Cite
|
Sign up to set email alerts
|

Creating a Stable Short-term Housing Environment for Rabbits in a Cargo Van

Abstract: Millimeter waves (MMW) have broad applications in highdata-rate communication systems (40 to 48 GHz), automotive radar sensors (77 GHz), high-resolution sensors for airport security (100 GHz), and spectroscopy (20 to 80 GHz). 4,6,14,21 Moreover, the recent trend in wireless communications is to use MMW with frequencies greater than 100 GHz (>100 GHz MMW) to transfer larger amounts of digital data. 1 The rapid development of technology has raised concerns about the possible influence of MMW on human health. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
1
0
0
Order By: Relevance
“…They were housed individually in stainless steel rabbit housing cages kept in a cargo van as short-term animal housing. Before starting this experiment, we confirmed that the cargo van animal housing did not differ from a conventional animal facility, at least for short-term housing [14].…”
Section: Experimental Animalssupporting
confidence: 56%
“…They were housed individually in stainless steel rabbit housing cages kept in a cargo van as short-term animal housing. Before starting this experiment, we confirmed that the cargo van animal housing did not differ from a conventional animal facility, at least for short-term housing [14].…”
Section: Experimental Animalssupporting
confidence: 56%